Transgenic Plant-Produced Hydrolytic Enzymes and the Potential of Insect Gut-Derived Hydrolases for Biofuels - Willis, Jonathan D.; Mazarei, Mitra; Stewart, C. Neal (Frontiers in Plant Science, 2016)
Various perennial C4 grass species have tremendous potential for use as lignocellulosic biofuel feedstocks. Currently available grasses require costly pre-treatment and exogenous hydrolytic enzyme application to break down complex cell wall polymers into sugars that can then be fermented into ethanol. It has long been hypothesized that engineered feedstock production of cell wall degrading (CWD) enzymes would be an efficient production platform for of exogenous hydrolytic enzymes. Most research has focused on plant overexpression of CWD enzyme-coding genes from free-living bacteria and fungi that naturally break down plant cell walls. Recently, it has been found that insect digestive tracts harbor novel sources of lignocellulolytic biocatalysts that might be exploited for biofuel production. These CWD enzyme genes can be located in the insect genomes or in symbiotic microbes. When CWD genes are transformed into plants, negative pleiotropic effects are possible such as unintended cell wall digestion. The use of codon optimization along with organelle and tissue specific targeting improves CWD enzyme yields. The literature teaches several important lessons on strategic deployment of CWD genes in transgenic plants, which is the focus of this review.